Pengaruh Rasio Derajat Desentralisasi, Rasio Ketergantungan Keuangan Daerah, Dan Rasio Tingkat Pembiayaan SiLPA Terhadap Alokasi Belanja Modal Pada Pemerintah Kabupaten/Kota Di Provinsi Jawa Barat - Yulistiani Marlianita; Suji Abdullah Saleh (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This research aimed to be examine the significant effect indicator of financial performance, namely the degree of decentralization ratio, dependency level ratio, and SiLPA financing rate ratio on the allocation ofc apital expenditure in the regencies/municipalities in West Java Province. The data used in this study was secondary data concisting Statement of Budget Realization of 27 regencies/municipalities in West Java Province 2014-2018 which were obtained from report of audit findings (LHP) by national Audit Board (BPK) of West Java Province. Data analysis method in this research used Random Effect Model (REM) by using Eviews 9 software. The results of this study show that simultaneously the degree of decentralization ratio, regional financial dependence ratio, and SiLPA Financing rate ratio has a significant effect on the allocation of capital expenditures. However, partially the degreeoof decentralization ratio and regional financial dependence ratio does not has a significant effect on the allocation of capital expenditure while the SiLPA financing rate ratio has a significant effect on the allocation of capital expenditure in regencies/municipalities in West Java Province with a coefficient determination value is 0.437352.